Using a COVID-19 Model in Various Classroom Settings to Assess Effects of Interventions. Issue 2 (7th February 2022) - Ledder, G.; Homp, M.
ABSTRACT: The COVID-19 pandemic has made mathematical epidemiology a topic of critical importance, providing mathematics educators with an unparalleled opportunity. This opportunity is accompanied by a challenge: how do mathematics educators, some of whom have little personal experience with mathematical modeling, teach mathematical epidemiology to their students in courses ranging from precalculus to differential equations, and do so in a way that builds understanding of epidemic disease dynamics as well as mathematical methods? We address this issue with a collection of materials that allow students to conduct virtual experiments with a COVID-19 model to assess the effects of public health policies and community behavior. The materials are designed to require only a bare minimum of coding by students so as to focus students' efforts on interpretation of results.